Her Depicted About 2021 / Nur Fatiyah Roslan - Roslan, Nur Fatiyah (Faculty of Art and Design, 2021)
Her Depicted About 2021 is one of my current digital illustration works in which I try to represent on how I feel and my expectation for this year, 2021. The bold swirl line is decoded as the puzzleness inside my under conscious mind. People put their dreams ahead even though they know it may change by consequences or luck, so the unexpected factor sometimes really irritates their feelings. On the other hand, the illustrated flowers represent my obsession creature which has become my natural therapy and remedy pills during my tough times. Illustrated shape of a woman overlapped with the other elements is a representation of myself on how these complementary elements and principles of life really complete my journey throughout this year.